Instructor’s Emotional Intelligence Improves Pilot Student’s Achievement at Akademi Penerbang Indonesia Banyuwangi - Yusuf Arta Wisuda; Dede Ardian; Hari Kurniawanto; Kukuh Tri Prasetyo (Technium Social Sciences Journal, 2024)
This study investigates the impact of Instructor Emotional Intelligence (IEI) on Pilot Student’s Academic Achievement (PSA) at the Indonesian Aviation Academy in Banyuwangi. A quantitative approach using a survey method was employed to collect data from 20 pilot students selected through purposive sampling. The main research instrument was a questionnaire designed to measure relevant variables, which was validated for reliability and accuracy. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the SmartPLS 3 software, allowing for examination within a small sample and complex model structure. The findings indicate a significant relationship between instructor emotional intelligence and pilot student academic achievement. Indicators such as emotion management, empathy, and instructor motivation contribute positively to enhancing pilot students’ academic performance. The loading factor and path coefficient values suggest that IEI has a strong influence on PSA, highlighting that students are more motivated and prepared to face academic challenges when guided by emotionally intelligent instructors. This study underscores the importance of instructors’ emotional skills in creating a supportive learning environment that can foster increased motivation and academic achievement among students. It recommends that aviation education institutions consider implementing emotional intelligence training for instructors to improve the quality of education and student learning outcomes.